Incidence and Growth of Patent Thickets - The Impact of Technological Opportunities and Complexity - Georg von Graevenitz; Stefan Wagner; Dietmar Harhoff (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2011)
We investigate incidence and evolution of patent thickets. Our empirical analysis is based on a theoretical model of patenting in complex and discrete technologies. The model captures how competition for patent portfolios and complementarity of patents affect patenting incentives. We show that lower technological opportunities increase patenting incentives in complex technologies while they decrease incentives in discrete technologies. Also, more competitors increase patenting incentives in complex technologies and reduce them in discrete technologies. To test these predictions a new measure of the density of patent thickets is introduced. European patent citations are used to construct measures of fragmentation and technological opportunity. Our empirical analysis is based on a panel capturing patenting behavior of 2074 firms in 30 technology areas over 15 years. GMM estimation results confirm the predictions of our theoretical model. The results show that patent thickets exist in 9 out of 30 technology areas. We find that decreased technological opportunities are a surprisingly strong driver of patent thicket growth.
urn:nbn:de:bvb:19-epub-13198-4
Keywords: L13; L20; O34; 330; Patenting; Patent thickets; Patent portfolio races; Complexity; Technological Opportunities; Patentrecht; Patent; Technischer Fortschritt; Branche; Ökonomischer Anreiz; Momentenmethode; EU-Staaten